Faktor-Faktor Pengalaman Konsumen Dan Electronic Word of Mouth Pada Konsumen Warung Sehat 1000 Kebun - Arini, Resti; Utami, Hesty Nurul (Universitas Galuh, 2024)
Changes in healthy lifestyles that occur in society cause the demand for organic vegetables to continue to increase. This is supported by the development of the use of social media which can support the exchange of product information or what is commonly called electronic word of mouth (E-WOM). A consumer-centered orientation can create a memorable experience for consumers so that they can exchange opinions about products with other consumers. This study aims to describe consumer characteristics and factors that provide good experiences to consumers so that they do E-WOM with others. The research method used is quantitative method with frequency distribution analysis. Data was collected using survey techniques and obtained 60 respondents. The results showed that consumer experience was most influenced by satisfactory service and the majority of consumers wanted to seek the opinions of others before they bought organic vegetable products at Warung Sehat 1000 Kebun.